2017
DOI: 10.1063/1.4978912
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the microwave annealing of silicon

Abstract: Though microwave annealing appears to be very appealing due to its unique features, lacking an in-depth understanding and accurate model hinder its application in semiconductor processing. In this paper, the physics-based model and accurate calculation for the microwave annealing of silicon are presented. Both thermal effects, including ohmic conduction loss and dielectric polarization loss, and non-thermal effects are thoroughly analyzed. We designed unique experiments to verify the mechanism and extract rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Moreover, the peak annealing temperature during the MWA process was determined to be below 344 °C, which is far below the lowest record of 400 °C using conventional thermal annealing methods [ 30 ], even when accounting for measurement errors produced by the infrared pyrometer [ 11 ]. Previous studies have demonstrated that the lower annealing temperature of the MWA process results from its unique non-thermal effect, which reduces the bonding activation energy during the recombination process [ 23 , 31 ]. Thus, a non-thermal effect could play a crucial role in reducing the temperature during nickel silicide formation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the peak annealing temperature during the MWA process was determined to be below 344 °C, which is far below the lowest record of 400 °C using conventional thermal annealing methods [ 30 ], even when accounting for measurement errors produced by the infrared pyrometer [ 11 ]. Previous studies have demonstrated that the lower annealing temperature of the MWA process results from its unique non-thermal effect, which reduces the bonding activation energy during the recombination process [ 23 , 31 ]. Thus, a non-thermal effect could play a crucial role in reducing the temperature during nickel silicide formation.…”
Section: Resultsmentioning
confidence: 99%
“…The mean projected range can also be determined from the location of the first crest of Al in Figure 4 , which appeared at the same position as the as-implanted Al peak. Given the deeper amorphous region produced by the higher implantation energy of Al, where strong rotation of dipoles occurs in response to the alternating electromagnetic field, the dielectric polarization loss effect was greatly induced [ 23 ], thereby enhancing absorption of microwaves during the MWA process. Combined with the intensified non-thermal effect reducing the dopant activation energy, the dopants were activated to a large extent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations